Pembuatan Game Shooter Edukasi Virus Komputer - Deryando Capringo; Agustinus Noertjahyana (Jurnal Infra, 2016)
Computer is a widely used device by everyone. Computer is used for many purposes such as: internet browsing, playing video games, music and videos, giving assistance for office works etc. Computer is also equipped with a very large storage system called hard drive. This equipment allows user to store large amount of their own data into the computer. The hard drive is also used for storing downloaded files from the internet. Computer viruses are programs that attacks computer via downloaded file from the internet. The purpose of this thesis’ creation is to help computer users to prevent various virus attacks. This thesis is made using Construct 2 an open source game development software that can be used even without basic programming knowledge. In this thesis there will be 4 types of games based on four types of viruses based on the activities they will do in the computer. With the creation of this thesis computer users can understand better about computer viruses and its prevention methods.